Identification, preclinical profile, and clinical proof of concept of an orally bioavailable pro‐drug of miridesap. (11th February 2020) - Richards, Duncan; Bamford, Mark; Liefaard, Lia; Haque, Nazneen; Lewis, Gareth; Storey, Jim; Fernando, Disala; Kumar, Subramanya; Thompson, Douglas; Holmes, Duncan S.
Abstract : Background and Purpose: Miridesap, a depleter of serum amyloid P component (SAP), forms an essential component of a novel approach to remove systemic amyloid deposits; low oral bioavailability necessitates that it is given parenterally. We sought to identify and clinically characterise a pro‐drug that preserves the pharmacological properties of miridesap while having adequate oral bioavailability and physical stability. Experimental Approach: We utilised a preclinical screening cascade focused on appropriate physicochemical properties, physical and gut stability, and conversion to miridesap in liver microsomes and blood. GSK3039294 (GSK294) had the desired in vitro profile and progressed to preclinical in vivo pharmacokinetic and safety assessments. Based on a favourable profile, it was tested in healthy participants after single and repeat dosing. Key Results: GSK294 was highly soluble and stable in simulated gastric and intestinal fluids, stable in intestinal microsomes, and permeable in Madine Darby Canine Kidney type II cells. GSK294 was rapidly hydrolysed to miridesap and its mono pro‐drug ester in blood and liver microsomes. GSK294 showed good oral bioavailability of miridesap in rats and dogs. Following administration of GSK294 600 mg QD for 7 days in humans, pharmacodynamically active concentrations of miridesap were achieved with substantial and sustained depletion of plasma SAP. The study was terminated due to observations of arrhythmia, the relation of which to GSK294 remains unclear. Conclusion and Implications: Using a preclinical screening cascade, we identified a pro‐drug for a palindromic molecule with unique pharmacology (miridesap). The pro‐drug depleted circulating SAP with a time course and extent similar to that of parenterally administered miridesap.